Monetary policy transmission in vector autoregressions: A new approach using central bank communication - Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
In this paper, we study the role central bank communication plays in the monetary policy transmission mechanism. We employ the Swiss Economic Institute's Monetary Policy Communicator to measure the future stance of the European Central Bank's monetary policy. Our results indicate that, first, communication influences prices and output. Second, communication partly crowds out the effects of the short-term interest rate as the latter's influence is lower and its implementation lag increases compared to a benchmark model without central bank communication. Future work on monetary policy transmission should incorporate both a short-term interest rate and a communication indicator.
Keywords: E52; E58; 330; central bank communication; European Central Bank; monetary policy shocks; monetary policy transmission; vector autoregression; Geldpolitik; Informationsverhalten; Staatliche Information; Transmissionsmechanismus; Makroökonomischer Einfluss; Europäische Wirtschafts- und Währungsunion; Eurozone